Optimizing Work-in-Process Inventory Management: Modern Approaches and Best Practices - Dinesh Kumar Garg, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The manufacturing industry faces significant challenges in Work-in-Process (WIP) inventory management, requiring innovative solutions to optimize operational efficiency. Traditional approaches to WIP management have proven inadequate in meeting the demands of modern manufacturing environments, particularly in handling back-flush complexities and dynamic production schedules. The implementation of operation-based counting methodologies, advanced ERP systems, and integrated technology solutions has transformed how organizations track and manage their WIP inventory. These modern approaches, combined with comprehensive BOM management and systematic auditing processes, enable manufacturers to achieve substantial improvements in inventory accuracy, production efficiency, and cost reduction. The integration of Industry 4.0 technologies, including IoT sensors and real-time monitoring systems, has further enhanced manufacturing capabilities through improved visibility and control. A structured implementation strategy, encompassing process analysis, systems modernization, workforce development, and continuous improvement mechanisms, provides a framework for organizations to successfully transition to advanced WIP management systems, resulting in enhanced operational performance, reduced material waste, and improved cash flow management.
Keywords: Manufacturing Optimization; Inventory Control; Digital Transformation; Production Efficiency; Resource Management